α-Diazoacetamides in Sc(OTf)3-Catalyzed Tiffeneau–Demjanov Ring Expansion: Application towards the Synthesis of Rare Bicyclic Pyrazoles - Chuprun, Sergey; Dar’in, Dmitry; Kantin, Grigory; Zhmurov, Petr; Krasavin, Mikhail (Synlett, 2020)
A novel Sc(OTf)3-catalyzed Tiffeneau–Demjanov ring expansion of six-membered cyclic ketones has been developed. The resulting seven-membered cyclic β-keto carboxamides were found to be versatile precursors to rare bicyclic pyrazoles obtained in modest to good yields via condensation with aryl hydrazines in the presence of Lawesson’s reagent.
Keywords: α-diazoacetamides; Tiffeneau–Demjanov ring expansion; scandium triflate; β-keto carboxamides; Lawesson’s reagent; bicyclic pyrazoles